Music, modernity, and the global imagination South Africa and the West - Erlmann, Veit.; Oxford eBooks (New York ; Oxford : Oxford University Press, 1999)
How do Western images of Africa and African representations of the West mirror each other? This study focuses on the tours of two black South African choirs in England and America in the 1890s, and the popularity of Ladysmith Black Mambazo since 1986.
Description based on print version record.
Includes bibliographical references and index.
Keywords: South African Choir; Zulu Choir; Ladysmith Black Mambazo (Musical group); Music -- South Africa -- Western influences; Music -- African influences; Intercultural communication; Ethnicity; Electronic books